Glibenclamide prescription services profile in pharmacies of the Tapung Hilir District - Hotvera Merianis, Hotvera; Razoki, Razoki; Ginting, Astriani Natalia Br (Buletin Kedokteran & Kesehatan Prima, 2025)
Prescription dispensing in pharmacies involves two key stages: screening and medication preparation. Screening, conducted by the pharmacist, covers administrative requirements, pharmaceutical suitability, and clinical considerations. Medication preparation includes compounding, labeling, packaging, dispensing, counseling, and monitoring. The overarching goal is to ensure that the medication prescribed is accurately and safely delivered to the patient. This study assessed the prescription service quality for glibenclamide in Tapung Hilir pharmacies. Ninety pharmacies were randomly sampled, and data were collected using a simulated patient approach, where researchers acted as patients' family members seeking glibenclamide. The instruments employed—prescription, scenario, protocol, and checklist—were validated for reliability. Results showed that 85 pharmacies (94.4%) dispensed the prescribed medication. However, patient information gathering was minimal: only 7.1% asked for the recipient’s identity, 18.8% for the patient’s address, and fewer than 5% inquired about prior medication use or understanding of administration. Critical clinical data such as patient age, symptomatology, therapy goals, concurrent medications, and allergy history were generally not obtained. On average, pharmacies asked only 0.4 out of 13 patient assessment questions. Regarding medication counseling, the frequency of drug use was explained by 42.4% of pharmacies, while other key information—indication, dose, side effects, treatment duration, and storage—was rarely provided. On average, only 1.2 out of 16 drug information items were communicated. Labels were provided by 65.9% of pharmacies, with only one using a distinguishable blue label. In conclusion, the involvement of pharmacy staff in the comprehensive provision of prescription services for glibenclamide remains limited in Tapung Hilir. Enhancement in patient assessment and information delivery is urgently needed to improve medication safety and effectiveness.